Eco-innovation paths: convergence or divergence? - Karman, Agnieszka; Kijek, Arkadiusz; Kijek, Tomasz (Technological and Economic Development of Economy, 2020)
Eco-innovations comprise new or modified processes, techniques, practices, systems and products allowing environmental harms to be avoided or reduced. They are employed in order for specific social and environmental objectives to be achieved, hence their environmental, social, and institutional significance relating to the achievement of long-term sustainable growth patterns. As a consequence, eco-innovation has great amount of focus from many countries. Adding to the current literature which focuses mainly on the drivers and effects of eco-innovation in the context of developed and developing countries, this paper tries to find an answer to the question about the absolute β-convergence of eco-innovation. We also consider the spillover effects in the analyses. Our sample consists of 38 countries and relates to the years 2012−2017. We apply the spatial panel models to verify the research hypotheses. The results confirm that there is the absolute β-convergence in the sample countries. Moreover, we find evidence of positive spillovers of eco-innovation.First published online 11 September 2020